Analytical and inorganic studies of new antitumor palladium (II), ruthenium II) and platinum (IV) complexes - Sattar Rajab Majeed Alessawi; Ahmed Soliman Abdellah; Fawzy Ali Attaby (Cairo : Sattar Rajab Majeed Alessawi, 2014)
Five rapid, simple, sensitive and validated spectrophotometric method has been described for the determination of palladium(II) using 3,4diaminobenzoic acid(DABA)(1),4-chloro{u2013}o-phenylenediamine (CPDA)(2) and 2-hydrazino pyridine (hzpy)(3) and both ruthenium(III)(4) and platinum(IV)(5) using 4-chloro{u2013}o-phenylenediamine(CPDA). The complexes product was quantitatively measured at 760 nm(1), 545nm(2), 510 nm(3), 560nm(4) and 715nm(5) and the reaction conditions were studied and optimized. The stoichiometry and the stability constant of the purple colored complexes have been determined spectrophotometrically in aqueous solution at 25 oC using Job{u2019}s continuous variation and the molar ratio methods. The complexes have The molar ratios (M:L) : 1:2(1), 1:2(2), 1:1(3), 1:1(4),1:2(5) and Beer{u2019}s plot was linear in the concentration ranges 1.06- 8.48(1), 2.21-10.6(2), 1.06-9.00(3), 2.00-12,36(4) and 1.95-27.30(5) og/mL with corresponding molar absorptivity 1.32{u00D7}10p4(B(1), 2.89{u00D7}10p3(B(2), 2.60{u00D7}10p3(B(3), 1.91{u00D7}10p3(B, 2.13{u00D7}10p3(B(5) , L/mol.cms
Thesis (Ph.D.) - Cairo University - Faculty of Science - Department of Analytical Chemistry
Issued also as CD
Keywords: 2- hydraziniopyridin Pt(IV); 3,4-diaminobinzoic; 4-chloro-o-phyelenediamin